Inclusive Pedagogy in Practice: Teaching English to Deaf and Mute Students in Elementary School - Sriadi, Kadek; Utami, I G A Lokita Purnamika; Budiarta, Luh Gd Rahayu (Journal of Educational Study, 2025)
This study explores the instructional procedures, challenges, and coping strategies involved in teaching English to deaf and mute students in an inclusive classroom. Although inclusive education continues to expand, English instruction for learners with hearing impairments remains difficult because of communication barriers and limited access to auditory input. This research uses a descriptive qualitative case study with participants consisting of two deaf and mute sixth-grade students, an English teacher, and a sign language teacher. Data were collected through classroom observations and semi-structured interviews and were analyzed using an interactive qualitative model. The findings show that English instruction followed three stages, namely pre activity, whilst activity, and post activity. Sign language, visual aids, and clear multimodal explanations played an important role in supporting comprehension. Teachers experienced challenges related to communication, differentiation, and classroom management, while students struggled with pronunciation, social interaction, and tasks that relied on sound. The study concludes that effective English instruction for deaf and mute learners requires adaptive, visually oriented, and collaborative teaching practices. These findings contribute to a clearer understanding of how inclusive classrooms can support equitable and meaningful language learning for students with hearing impairments